The Developmental Plasticity of Boldness and Aggressiveness in Juvenile and Adult Swimming Crab (Portunus trituberculatus) - Liang, Qihang; Su, Xianpeng; Wang, Fang; Zhu, Baishan; He, Mingdi (Frontiers in Marine Science, 2020)
Boldness and aggressiveness are crucial behavioural traits in the field of animal personality, and both have important ecological and evolutionary significance. As swimming crabs (Portunus trituberculatus) are aggressive, their production is affected; thus, it is important to study their behaviour. To assess the relationship between boldness and aggressiveness of male P. trituberculatus and the differences between their life stages, we determined the individual differences in these two traits in juvenile and adult crabs under laboratory conditions. Based on the k-means cluster analysis, boldness of crabs is classified according to their rush to adventure, and aggressiveness of crabs is classified according to their aggressive behaviour towards conspecifics. The results show that the personality classification of juvenile and adult crabs was consistent. Boldness can be divided into three levels: bold, middle, and shy. Aggressiveness could be divided into two levels: aggressiveness and non-aggressiveness. The personality of juveniles and adults P. trituberculatus was significantly different; juveniles presented higher aggressiveness and lower boldness than adults. Additionally, a significant positive correlation between boldness and aggressiveness of adult crabs was verified (P=0.001, ρ=0.271). However, this correlation in juvenile crabs was not significant (P=0.702, ρ=0.042). These preliminary results indicate that the personality of P. trituberculatus has developmental plasticity and adults have the boldness-aggressiveness behavioural syndrome.